How new is the new biography? Some remarks on the misleading term’s past and present - Cymbrykiewicz, Joanna (Studia Europaea Gnesnensia, 2018)
The article discusses the issue of the so-called “new biography” by underscoring ambiguity of the term and presenting the different variants of “new biography” it encompasses. In order to do that, an introduction is made where the tenets of the classical biography are outlined. The inquiry focuses chiefly on England and the USA, although remarks are also made with respect to biographical writing in other countries. It appears that the term is contemporarily mainly associated with Lytton Strachey’s model of biography which, having been formulated in 1918, proved a breakthrough in life writing, since it operated with ironic detachment from the protagonist. Strachey perceived biography as an art and was determined to speak openly about all spheres of the biographee’s life. The article proves that although other attempts at creating a “new biography” were made after Strachey (by Leon Edel and Jo Burr Margadant), their newness is either derivative and supplementary to Strachey’s achievement, or advances a wholly new notion of biography, with the concept of multiplicity of the protagonist’s self. As the Stracheyan biographical model is almost a century old, one can assume that what is understood as “new biography” is not so new after all. In the meantime, though, biographical practice has taken a turn and a novelistic mode of writing, i.e. biofiction, has become the current paradigm. The author therefore suggests that the present-day understanding of “new biography” be reconsidered by recognizing biofiction as one of the figures of biographical “newness”.